UPAYA PENANGANAN KONFLIK SOSIAL DI KALIMANTAN TIMUR - Yuniarti Yuniarti (Magister Administrasi Publik FISIP Universitas Mulawarman, 2018)
This article explains the causes of conflict and the efforts of conflict settlement in East Kalimantan in three areas, i.e. Samarinda, Balikpapan, and Kutai Timur. This is a descriptive qualitative research using primary and secondary data by depth interview and literature study. The results shows that based on the Druckman Approach, the conflicts in Samarinda, Balikpapan and Kutai Timur are attributable to three resourses of conlicts those are interest conflict (economic and politic), understanding conflict (social and cultural gap), and ideology conflict (religion and believe, except that of Balikpapan). Meanwhile, the effort of conflict settlement is conducted by Social Conflict Respon Team which is consist of government and society elements. The team uses persuasive approach, mediation. Mediation would be consist of two stages, investigation and solution. There are two solutions would be possible. First, if the team found that there is a criminal case so legal approach will be implemented. Second, if the team found that there is no criminal case so humanity approach based on local wisdom would be implemented. The latter is more efective to dealt with the social conflit since the trust of people toward their traditional/cultural/religion leader much bigger than toward the aparatus.Keywords: social conflict, conflict settlement, East Kalimantan